Marsvins naturliga miljö och beteende - Melin, Ingrid (2017)
The wild guinea pigs (Cavia aperea) are native to the South African grasslands and savannahs where they live in small family groups often lasting their whole life. They were domesticated for several thousand years ago and are now popular pets all over the world. Still, the information available about domesticated guinea pigs (Cavia porcellus) needs could be better. Guinea pigs have personalities of their own and are friendly and docile creatures in need of a suitable environment in captivity. Their groups in the wild are made up of one male, his one to two females and their unweaned offspring. In captivity several males and females can live together if they have enough space and they form linear dominance hierarchies. They also form strong bonds between them which can result in stress if broken because of separation. Females have long pregnancies and give birth to highly developed pups which becomes sexually mature around 2-3 months. During this time the environment they are growing up in is crucial to their behavioural development. And to make them easy to house with other guinea pigs later in life, rich and stable social conditions are important. Guinea pigs also need places to hide, preferably in big piles of hay or straw, but also in sturdy houses. They also need a constant easy supply of hay served in a natural position. Their cage can be furnished with logs, branches, twigs, rocks and other natural materials to simulate a natural environment and their pellets should be spread around the cage instead of being served in a bowl. Their cage-space should also be big enough to offer plenty of exercise and enable foraging behaviour. These are all some important factors to considerate when keeping guinea pigs in captivity.